Alkyne [2+2+2]-cyclotrimerization approach for synthesis of 6,7-cyclopropylallocolchicinoids - More, Atul A.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2016)
Employing a cobalt-catalyzed [2 + 2 + 2] alkyne cyclotrimerization as the final step, the short and efficient synthesis of cyclopropylallocolchicinoid and its analogues having functional group variations at C9 and/or C10 and C11 of ring C has been accomplished.

Apparent umpolung reactivity of indole through [Au]-catalysed cyclisation and lewis-acid-mediated allylation - Shinde, Mahesh H.; Ramana, Chepuri V. (Chemistry-A European Journal, 2020)
The sequential functionalization of indole C2 and C3 in an umpolung fashion was executed with a predesigned substrate and choice of reagents. The developed method comprises gold-catalysed alkynol cycloisomerisation/intramolecular addition of C2 of indole and subsequent BF3.OEt2-mediated regioselective C3 allylation, resulting in the synthesis of the functionalized indoloisoquinolinone scaffold. The reaction involves 5-endo-alkynol cycloisomerisation and the dearomative addition of indole C2 to the intermediate oxocarbenium cation, which results in two equilibrating fused and spiropentacyclic intermediates, which upon treatment with allyl silane in the presence of BF3.OEt2, undergo selective indole C3 allylation. Other nucleophiles, such as hydride, azide and indole, were also found to be compatible with this process.
Keywords: Allylation; cyclization; domino reactions; Gold; umpolung

Attempted synthesis of the central 2,2-disubstituted pseudoindoxyl core of Austamide via a [Au]-catalyzed nitroalkyne cycloisomerization and intramolecular [3+2]-cycloaddition - Halnor, Swapnil V.; Ramana, Chepuri V. (Tetrahedron, 2024)
Herein, we describe an Au-catalyzed cycloisomerization process of a nitroalkyne that was projected to construct the central 2,2-disubstituted pseudoindoxyl core of the natural product Austamide. Our intended strategy for forging the pseudoindoxyl core is based on the nitroalkyne cycloisomerization followed by a subsequent intramolecular [3 + 2] cycloaddition. However, the [3 + 2] cycloaddition occurred in an undesired manner, ultimately leading to a complex hexacyclic scaffold.
Keywords: Austamide; Gold catalysis; Intramolecular [3+2] cycloaddition; Nitroalkyne cycloisomerization